DLC films deposited on rubber substrates: a review. (January 2015) - Lubwama, M.; Corcoran, B.; Sayers, K.
<x content-type="archive" xml:space="preserve">Abstract</x> An extensive review on the characteristics of diamond-like carbon (DLC), doped DLC and DLC multilayer films deposited on rubber substrates is presented. Typical deposition technologies used for depositing DLC films on rubber substrates are mentioned. Methods used in characterising DLC films deposited on rubber substrates are presented. The review shows that no film property or characteristic has been discussed in more than 14 publications to-date. Therefore, further research is required on characterisation of chemical composition, chemical bonding, surface roughness, hydrophobicity, surface energy, adhesion, flexibility, electrical resistance, hardness and wear. Raman spectroscopy analysis is a powerful non-destructive method for determining the chemical bonding, intensity ratios, peak positions, multi-wave length analysis, residual stress analysis and bonded hydrogen analysis in the films. Different studies have reported different values for these Raman parameters. The surface morphology for DLC films deposited on rubber substrates is dendritic. Inconsistencies between columnar and non-columnar microstructures for DLC films deposited on rubber substrates at different bias voltages exist in the literature. There is general consensus on DLC films deposited on rubber substrates being hydrophobic. Diamond-like carbon films deposited on rubber substrates exhibit good adhesion due to the powdery rough morphology of the rubbery substrate and the development of polymer like chains. The deformation of the rubber substrate has hindered progress on the determination of actual hardness values for DLC films deposited on rubber substrates. Diamond-like carbon films deposited on rubber substrates are generally characterised by low frictional coefficients and low wear rates. However, because of the differences in DLC film composition, morphology, processing and microstructure, a continuous characterisation effort is necessary so that inconsistencies identified in the literature can be resolved.